Combining Crude Glycerin with Chitosan Can Manipulate In Vitro Ruminal Efficiency and Inhibit Methane Synthesis - Anuthida Seankamsorn; Anusorn Cherdthong; Metha Wanapat (Animals, 2019)
It was hypothesized that the combination of glycerin and chitosan improves ruminal fermentation efficiency via an enhanced propionate (C3) and reduces in vitro CH4 production. This was explored through in vitro gas production with substrates containing crude glycerin, which replaced cassava chips in the studied ration. The experimental design was organized following a 3 × 3 factorial in completely randomized design and the arrangement of treatments were different levels of crude glycerin supplementations 0, 10.5, and 21% of total mixed ration (TMR) and chitosan levels were added at 0, 1, and 2% dry matter (DM) of substrate. Then, 0.5 g of TMR substrates were added into 40 mL bottles, together with respective doses of chitosan and then incubated at 39 °C. The dietary treatments were performed in three replicates within the incubation, and incubations were repeated on three separate days (runs). No interactions were found between crude glycerin and chitosan doses in terms of theoretical maximum of asymptotic gas production (b), rate of gas production (c), the discrete lag time prior to gas production (L), or the cumulative gas production at 96 h of incubation (p > 0.05). Cumulative gas production at 96 h of incubation was similar among the doses of crude glycerin and levels of chitosan, which ranged from 64.27 to 69.66 mL/g DM basis of substrate (p > 0.05). The concentration of ruminal NH3-N after 2 and 4 h of incubation ranged from 14.61 to 17.10 mg/dL and did not change with the addition of crude glycerin with chitosan (p > 0.05). The concentration of CH4 after 2 h of incubation did not change among treatments (p > 0.05), whereas after 4 h of incubation, CH4 synthesis was significantly reduced by enhancing doses of crude glycerin and chitosan (p < 0.05). The combination of 21% of crude glycerin in TMR with 2% chitosan depressed CH4 production as much as 53.67% when compared to the non-supplemented group. No significant crude glycerin and chitosan interaction effect was detected for in vitro digestibility of nutrients after incubation for 12 and 24 h using the in vitro gas production technique (p > 0.05). In addition, no significant changes (p > 0.05) were observed in total volatile fatty acids, acetate (C2) or butyrate content among treatments and between the main effects of crude glycerin with chitosan. At 4 h of incubation, ruminal C3 content and the C2 to C3 ratio changed significantly when crude glycerin and chitosan was added (p < 0.05). The 21% crude glycerin incorporate into TMR, in combination with 2% additional chitosan, increased C3 content by 26.41%, whereas the ratio of C2 to C3 was reduced by 31% when compared to the control group. Propionate concentration increased by 11.75% when increasing levels of chitosan at 2% of substrate, whereas the C2 to C3 ratio decreased by 13.99% compared to the 0% chitosan group. The inclusion of crude glycerin at 21% in TMR diets with chitosan supplementation at 2% enhanced ruminal propionate concentration and reduced methane production without causing any detrimental effect on the gas kinetics or nutrient digestibility.